Directionally generalized differentiation for multifunctions and applications to set-valued programming problems - Thinh, Vo Duc; Chuong, Thai Doan (Annals of operations research, 2018)
The aim of this work is twofold. First, we establish sum rules for the directionally coderivatives of multifunctions and intersection rules for the directionally limiting normal cones. Then, we apply the provided formulas to derive directionally necessary conditions for a set-valued optimization problem with equilibrium constraints.